Heat Integration Strategies for Acetaldehyde Production: Optimizing Ethanol Dehydrogenation and Hydrogen Recovery - Faruq Naufal Yusuf; Muhammad Abiyyu Biantoro; Muhammad Faishal Mujahid; Hafidz Azwar Rahim; Elleonora Pramusita Prawira (Journal of Chemical Engineering Research Progress, 2025)
Acetaldehyde production via ethanol dehydrogenation is inherently energy-intensive due to its endothermic characteristics, while the hydrogen generated as a co-product must achieve high purity to meet industrial specifications. Enhancing energy efficiency and hydrogen quality is therefore essential to advancing the sustainability and economic feasibility of this process. This study investigates strategies to optimize energy consumption and hydrogen purity in acetaldehyde production through systematic heat integration and absorber operating condition optimization. Process simulations were employed to quantify the influence of internal heat exchanger integration on overall heat demand and to examine the effect of absorbent flow rate variation on hydrogen purification performance. Integration of heat exchangers reduced total energy consumption by "10,148,446.64" kJ/h, corresponding to a 23% improvement in energy efficiency. Moreover, increasing the absorber water flow rate elevated hydrogen purity from 94.6% to 99.5%. The combined optimization decreased specific energy consumption to 34,316,959.07 kJ/h and lowered monthly operating costs by 22.8%. These findings demonstrate that coupling heat integration with absorber flow rate optimization constitutes an effective approach to improving energy efficiency, hydrogen quality, and economic viability in acetaldehyde production via ethanol dehydrogenation. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).